2015 ACC/AHA/HRS Advanced Training Statement on Clinical Cardiac Electrophysiology (A Revision of the ACC/AHA 2006 Update of the Clinical Competence Statement on Invasive Electrophysiology Studies, Catheter Ablation, and Cardioversion). (December 2015) - Zipes, Douglas P.; Calkins, Hugh; Daubert, James P.; Ellenbogen, Kenneth A.; Field, Michael E.; Fisher, John D.; Fogel, Richard Ira; Frankel, David S.; Gupta, Anurag; Indik, Julia H.; Kusumoto, Fred M.; Lindsay, Bruce D.; et al.
Abstract : Supplemental Digital Content is available in the text.